Reduced Pharma Supply Chain in COVID-19: Measures to Reduce India’s Reliance for Active Pharmaceutical Ingredients on China and other Countries - Vyas, Narendra; Joshi, Ankur; Malviya, Sapna; Kharia, Anil (Indian Journal of Pharmaceutical Education and Research, 2020)
India, which is called the “world of pharmacy” for being a top supplier of medicines in several countries, can depend on other countries for Active Pharmaceutical Ingredients (API) and other raw materials. Although India is one of the major suppliers of high-quality medicines in several countries, the Indian pharmaceutical industry is highly dependent on China and other countries in terms of raw materials (including the production of essential medicines such as Crocin). These raw materials are called Active Pharmaceutical Ingredients (API), also known as loose drugs. Indian pharmaceutical manufacturers import medicines from China and other countries/regions to account for about 70% of total medicine demand. This article sheds light on the important question of how India depends on other countries to obtain API and other raw materials. Also, the effect of COVID-19 pandemic on the supply chain of bulk drugs, which indirectly affects the pharmaceutical manufacturers. The article concludes that this is the right time for India to remove the dependencies for bulk drugs on china and other countries and start producing their own API in the country itself. COVID-19 situation provides India an opportunity to become a preferred alternate hub for manufacturing APIs and intermediates.
Keywords: Active Pharmaceutical Ingredients; Imports of API; Imports from China; COVID-19; Bulk drugs; Opportunity for India